(untitled) (Italian Journal of Public Health, 2004)
In accordance to the WHO-CINDI (Countrywide Integrated Non-communicable Diseases Intervention) Programme, in 2001-2002 Italy participated in the Health Monitor Survey (HMS) along with all the other CINDI member countries. The survey aimed to investigate, by the use of a standard questionnaire, the self-reported health status, life-habits, social and health conditions, use of health services and other features of the study population. Following the international CINDI protocol, the adult population (25-64 years of age) from six Italian demonstration areas were chosen: Bassiano-Lenola (LT), Brisighella (RA), Rovescala (PV), Sardinia (CA, SS), Udine (UD); Valle dell’Irno (SA). A total number of 4095 subjects, including both males and females were enrolled, with a participation rate of 53%, equal to 2202 subjects [45.7% males (M) and 54.3% females (F)]. All age groups were equally represented. From the analysis of the age-standardised rates, the following results were obtained. Self-reported “good state of health”: M 71%, F 56.9%; Hypertension: M 15.6%, F 17.5%; Diabetes: M 6.1%, F 4.2%; Back-illness: M 18%, F 22%; Gastritis: M 12.8%, F 12.6%; Headache: M 31.7%, F 54.6%; Insomnia: M 15.9%, F 28.5%; Daily smokers: M 35.7%, F 23.5%; Daily consumption of wine: M 40.2%, F 15.7%; BMI ≥ 30: M 12.3%, F 13.5%; Regular leisure physical activity: M 27.6%, F 23.1%; Hard physical activity: M 40.5%, F 24%. The results demonstrate how rural areas (Rovescala and Valle dell’Irno) experience worse health conditions. Thanks to the HMS, the population’s health needs have been focused and compared to those of other CINDI countries, in order to plan specific interventions aimed at the improvement of lifestyle and health conditions.